2018
DOI: 10.1371/journal.pone.0196122
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lactic acidosis in type 2 diabetes patients using metformin: A case control study

Abstract: BackgroundMetformin constitutes first-line treatment of type 2 diabetes mellitus. It is presumed to have lactic acidosis as a dangerous, but rare, side effect.ObjectivesTo estimate the incidence rate of lactic acidosis in patients with type 2 diabetes mellitus as well as to estimate the relative risk of lactic acidosis associated with metformin treatment.MethodsThis is a population-based combined cohort and case-control study among patients with type 2 diabetes mellitus who were acutely admitted with lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
3
25
0
1
Order By: Relevance
“…These ndings are partly in line with the results described in a UK population cohort study on the same group of patients (adjusted HR: 6.06, 95% CI: 1.37-27.10) [7]. Conversely, metformin use has not been associated with an increased risk of LA in other studies [5] [12] [13]. It should be noted that recommendations on the use of metformin in patients with CKD are based on observational studies, which could represent a limitation for its endorsement [3,4].…”
Section: Discussionsupporting
confidence: 85%
“…These ndings are partly in line with the results described in a UK population cohort study on the same group of patients (adjusted HR: 6.06, 95% CI: 1.37-27.10) [7]. Conversely, metformin use has not been associated with an increased risk of LA in other studies [5] [12] [13]. It should be noted that recommendations on the use of metformin in patients with CKD are based on observational studies, which could represent a limitation for its endorsement [3,4].…”
Section: Discussionsupporting
confidence: 85%
“…Patients with low eGFR may suffer from a range of systemic complications simultaneously, and metformin accumulation is probably not the cause of lactic acidosis in these subjects in most cases . This is also supported by the work by Aharaz et al who found no relation between metformin and neither the incidence rate of or risk of acute hospitalization with acute lactic acidosis. Notable is, however, that the most extreme subjects with moderate to severe (45‐59 mL/min/1.73 m 2 ) and mild to moderate (60‐89 mL/min/1.73 m 2 ) kidney impairment were according to the simulations at risk of overexposure.…”
Section: Discussionmentioning
confidence: 73%
“…3,4 The main safety concern for metformin is an elevated risk of lactic acidosis, which has been shown to be loosely or unrelated to metformin plasma concentrations above 5 mg/L. [5][6][7] Finding predictive markers of variability would aid tailoring metformin therapy and potentially improve metformin efficacy and safety. At physiological pH, metformin is protonated and relies on transporters to cross membranes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the strength of the relationship between metformin and lactic acidosis has been dramatically overstated [4]. Several clinical studies have shown that there is no significant correlation between metformin concentration and lactic acidosis [1,4,[30][31][32]. Furthermore, the current study and meta-analyses show that the morbidity of lactic acidosis using metformin is not significantly different from other hypoglycemic treatments, such as sulfonylureas, insulin, and other oral hypoglycemic agents [33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 74%
“…As the first-line therapy of type 2 diabetes mellitus (T2DM), metformin is applying to nearly one-third of diabetes patients worldwide [1]. Therefore, in urgent situations, such as acute myocardial infarction, many of them cannot withhold the metformin prior to percutaneous coronary intervention (PCI)-related contrast medium administration [2].…”
Section: Introductionmentioning
confidence: 99%